Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1991
DOI: 10.1090/s0002-9947-1991-1002923-0
|View full text |Cite
|
Sign up to set email alerts
|

The holomorphic discrete series of an affine symmetric space and representations with reproducing kernels

Abstract: Abstract. Consider a semisimple connected Lie group G with an affine symmetric space X . We study abstractly the intertwining operators from the discrete series of X into representations with reproducing kernel and, in particular, into the discrete series of G ; each such is given by a convolution with an analytic function. For X of Hermitian type, we consider the holomorphic discrete series of X and here derive very explicit formulas for the intertwining operators. As a corollary we get a multiplicity one res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 19 publications
(20 reference statements)
0
11
0
Order By: Relevance
“…The fact that z(k) ⊆ q implies that we can choose ∆ C is injective and via this inclusion mapping we identify in the sequel a * C with a subspace of t * C . For a H ∩ K-spherical highest weight λ ∈ a * ⊆ it * the condition for L(λ) to belong to the relative holomorphic discrete series of G/H is given by [29], [19]; see also [24] …”
Section: Theorem 51 There Exists a Weakly Holomorphic Map C → S V mentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that z(k) ⊆ q implies that we can choose ∆ C is injective and via this inclusion mapping we identify in the sequel a * C with a subspace of t * C . For a H ∩ K-spherical highest weight λ ∈ a * ⊆ it * the condition for L(λ) to belong to the relative holomorphic discrete series of G/H is given by [29], [19]; see also [24] …”
Section: Theorem 51 There Exists a Weakly Holomorphic Map C → S V mentioning
confidence: 99%
“…Discrete series on G/H were constructed in [12] (see also [30]) and in [3] it was shown that (H −∞ ) H is one-dimensional for all discrete series on G/H except for four types of exceptional symmetric spaces. Holomorphic discrete series, i.e., unitary highest weight representation of G which can be realized in L 2 (G/H), were constructed in [28], [29] (this construction is essentially different from the one in [12]) and it was shown that (H −∞ ) H is always one-dimensional (this also covers half of the exceptional spaces in [3]). …”
Section: Introductionmentioning
confidence: 99%
“…The first deep results in this direction are due to Ol'shanskii [80] and Stanton [98], who realized the holomorphic discrete series of the group G in a Hardy space of a local tube domain containing G in the boundary. The generalization to noncompactly causal symmetric spaces was carried out in [33,34,75,76].…”
Section: Holomorphic Representationsmentioning
confidence: 99%
“…What it does not do is give a natural analytic construction of the inner product on H(Ω C , W λ ). This is known only for some special representations, e.g., the holomorphic discrete series of the group G c [23,7,35] or symmetric spaces of Hermitian type [75,76]. At this point we will only discuss the holomorphic discrete series, which was constructed by Harish-Chandra in [23], in particular Theorem 4 and Lemma 29.…”
Section: )mentioning
confidence: 99%
“…The image of β is given by the direct sum of the holomorphic discrete series constructed in [17,18]. Let π be an irreducible unitary representation of K on the finite dimensional Hilbert space V π .…”
Section: The Hardy Spacesmentioning
confidence: 99%